2000
DOI: 10.1007/s001670000149
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon rupture: experimental results on spontaneous repair in a sheep‐model

Abstract: We studied the course of spontaneous healing of Achilles tendons in a sheep model after transection and partial resection of the tendon by means of histological and biomechanical analyses. In 18 sheep used for another animal study the operated knee had to be excluded from weight-bearing; therefore the Achilles tendons were transected and for 1.5 cm partially resected in the middle substance of the tendon. For evaluation these spontaneously healed tendons (n = 18) were compared with the contralateral noninvolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 26 publications
2
78
0
1
Order By: Relevance
“…32 Other studies using a sheep model to study the spontaneous repair of ruptured Achilles tendon found that, after 3 months and 12 months, the total rupture force of the injured tendon was about 75.6% and 81.18%, respectively. 1 Regardless of the surgical method or model used, these studies showed that a long period of time is required for the recovery of the biomechanical properties of an injured tendon. In clinical situations, especially for elite athletes, the strength of an Achilles tendon after rupture and repai, may not return to its original level, hindering the athletes' to return to their original level of activity, even after a long period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Other studies using a sheep model to study the spontaneous repair of ruptured Achilles tendon found that, after 3 months and 12 months, the total rupture force of the injured tendon was about 75.6% and 81.18%, respectively. 1 Regardless of the surgical method or model used, these studies showed that a long period of time is required for the recovery of the biomechanical properties of an injured tendon. In clinical situations, especially for elite athletes, the strength of an Achilles tendon after rupture and repai, may not return to its original level, hindering the athletes' to return to their original level of activity, even after a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The medial tendon, including the musculo-tendinous junction, was dissected and fixed in a 4% phosphatebuffered paraformaldehyde solution at room temperature. 1 After dehydration in graded ethanol, specimens were embedded in paraffin and then cut in 5-mm thick longitudinal sections. The sections were stained with Ehrlich's hemotoxylin/eosin (HE).…”
Section: Biomechanical Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of studies on horses, rabbits, and rats 39,40,[51][52][53][54][55][56] , given that obtaining human biopsy samples can be difficult, it has been shown that following tendon injury, the natural healing process forms scar tissue via a three-stage process: inflammation, matrix production, and remodeling and maturation 39,40 . The inflammatory stage initiates the response to injury, typically throughout the first week 39 .…”
Section: Natural Healingmentioning
confidence: 99%
“…Cell density and vascularity decrease as the tissue further repairs 40 . Studies have shown that natural healing leads to tendon biomechanical properties that fail to match normal levels at up to eight weeks, twenty-six weeks, and twelve months following injury in a murine and rabbit central patellar tendon model, and sheep Achilles tendon model, respectively [51][52][53] . Investigators have suggested the poor mechanical properties result from predominantly small fibrils in the resulting repair tissue, compared with the normal distribution of both large and small fibrils observed in normal adult human tendon 54,55 , but conflicting results exist.…”
Section: Natural Healingmentioning
confidence: 99%